2012
DOI: 10.1007/s00441-011-1308-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and evaluation of biomimetic-synthetic nanofibrous composites for soft tissue regeneration

Abstract: Electrospun scaffolds hold promise for the regeneration of dense connective tissues, given their nanoscale topographies, provision of directional cues for infiltrating cells and versatile composition. Synthetic slow-degrading scaffolds provide long-term mechanical support and nanoscale instructional cues; however, these scaffolds suffer from a poor infiltration rate. Alternatively, nanofibrous constructs formed from natural biomimetic materials (such as collagen) rapidly infiltrate but provide little mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…As outlined above, we have demonstrated that both silk and collagen can be co-spun with synthetic nanofibers to create biopolymer composites with both mechanical integrity and flexibility in post-processing [72,96,173]. Collagen/PCL nanofiber composites are more biomimetic than pure PCL and can improve the initial cellularity of composites [173].…”
Section: Multifiber Scaffoldsmentioning
confidence: 81%
See 1 more Smart Citation
“…As outlined above, we have demonstrated that both silk and collagen can be co-spun with synthetic nanofibers to create biopolymer composites with both mechanical integrity and flexibility in post-processing [72,96,173]. Collagen/PCL nanofiber composites are more biomimetic than pure PCL and can improve the initial cellularity of composites [173].…”
Section: Multifiber Scaffoldsmentioning
confidence: 81%
“…As outlined above, we have demonstrated that both silk and collagen can be co-spun with synthetic nanofibers to create biopolymer composites with both mechanical integrity and flexibility in post-processing [72,96,173]. Collagen/PCL nanofiber composites are more biomimetic than pure PCL and can improve the initial cellularity of composites [173]. The Wagner group also established that multifiber mats can be functionalized to release drugs or growth factors by using one family to act as a stable template (PEUU nanofibers), while a second family (PLGA) can be used to deliver active antibiotics [42].…”
Section: Multifiber Scaffoldsmentioning
confidence: 90%
“…Tubular scaffolds (5 cm long) were immersed in a HuBiogel solution (1 mg/mL in the phosphate buffered saline, PBS) for 24 h and then kept at 37 °C for 2 h for gelation. Crosslinking of proteins using both Gp and EDC was carried out in solution-phase [6, 12]. Scaffolds were soaked in 200 mM solutions of Gp in pure ethanol or EDC in pure ethanol for 24 h. After crosslinking the mechanical, structural, and morphological characterization, as well as coating stability studies, were carried out for PCL/PGC, biohybrid (HB coated), and crosslinked scaffolds.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed for fibre-based materials, the mechanical properties are affected by the polymer molecular weight, morphology, crystallinity, as well as the material size and shape such as porosity, pore area and fibre size, density and orientation [44]. For instance, when electrospun fibre-based materials are developed with aligned fibres, the modulus and the tensile strength increase and the mechanical behaviour becomes anisotropic in comparison to randomly arranged fibres [62,63]. The fibre size also affects the mechanical properties as a reduction in the size improves the orientation and decreases the quantity of defects in the structure.…”
Section: Propertiesmentioning
confidence: 99%